2015
DOI: 10.1002/dta.1861
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and analytical characterizations of N‐alkyl‐arylcyclohexylamines

Abstract: Abstract:The rise in new psychoactive substances that are available as 'research chemicals' (RCs) remains a significant forensic and legislative challenge. A number of arylcyclohexylamines have attracted attention as RCs and continued to be encountered, including 3-MeO-PCP, 3-MeO-PCE and 3-MeO-PCPr. These compounds are commonly perceived as ketamine-like dissociative substances and are believed to act predominantly via antagonism of the N-methyl-D-aspartate (NMDA) receptor. To aid in the identification of newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…The six morpholine analogues investigated in this study (Figure B) were synthesized using the modified Geneste route as reported previously for the preparation of PCP and PCPy analogues . The conversion from the primary amine (PCA) to the morpholine ring was performed using an S N 2 cyclization reaction between the substituted PCA material and bis(2‐bromoethylether) (Figure ) and gave ~ 45% yields following purification by column chromatography and recrystallization.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The six morpholine analogues investigated in this study (Figure B) were synthesized using the modified Geneste route as reported previously for the preparation of PCP and PCPy analogues . The conversion from the primary amine (PCA) to the morpholine ring was performed using an S N 2 cyclization reaction between the substituted PCA material and bis(2‐bromoethylether) (Figure ) and gave ~ 45% yields following purification by column chromatography and recrystallization.…”
Section: Resultsmentioning
confidence: 99%
“…The syntheses of the primary amine intermediates were performed using a modified Geneste route (Figure ) as described previously . Reactions starting from the primary amine intermediate to yield the morpholine ring products were carried out in a CEM Discover SP microwave synthesizer.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations